Identification Of Traditional Foods In West Pasaman District - Ayuni, Indah Muthia; Kasmita, Kasmita; Yuliana, Yuliana; Gusnita, Wiwik (Universitas Negeri Padang, 2024)
This study aims to learn more about traditional food in West Pasaman District. The research was conducted August-December 2023 in West Pasaman District.The purpose of this study was to identify the types of food, ingredients used and traditional food processing techniques in West Pasaman District. The type of research used is a mix method (qualitative and quantitative). This research data was obtained from two ways, namely primary data and secondary data. Primary data was conducted to identify the types of traditional food, ingredients used and traditional food processing techniques in West Pasaman District. While secondary data is in the form of demographics of West Pasaman District. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis is done by reducing data, presenting data, and concluding. The conclusion of the research results is that traditional food in West Pasaman Regency is a typical food that has existed for a long time. The ingredients used are food ingredients developed by yourself. As well as traditional food processing techniques that are typical in West Pasaman District.